Answer:
Option B
Explanation:
Option A
a² - b² = (a+ b)(a - b)
It's a polynomial identity.
Option B
a³ + b³ = (a - b)(a² - ab + b²)
It's not a polynomial identity.
Because the identity is,
a³ + b³ = (a + b)(a² - ab + b²)
Option C
a³ - b³ = (a - b)(a² + ab + b²)
It's a polynomial identity.
Option D
(a²+ b²)(c² + d²) = (ac - bd)² + (ad + bc)²
= a²c² - 2abcd + b²d² + a²d² + b²c² + 2abcd
= a²c² + b²c² + b²d² + a²d²
= c²(a² + b²) + d²(a² + b²)
= (a²+ b²)(c² + d²)
Therefore, it's a polynomial identity.
Option B will be the answer.